2016
DOI: 10.1007/s00018-016-2177-2
|View full text |Cite
|
Sign up to set email alerts
|

The M. tuberculosis HAD phosphatase (Rv3042c) interacts with host proteins and is inhibited by Clofazimine

Abstract: Mycobacterium tuberculosis codes for a HAD-phosphatase, Rv3042c (MtSerB2), that has earlier been characterized as a metabolic enzyme. Here we demonstrate that MtSerB2 is secreted into the cytosol of infected macrophages and is found in bronchoalveolar lavage samples of tuberculosis patients. MtSerB2 induces significant cytoskeleton rearrangements through cofilin activation and affects the expression of genes that regulate actin dynamics. It specifically interacts with HSP90, HSP70 and HSP27 that block apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 58 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…SerB2 is the most recent addition in the repertoire of Mtb's secreted virulence factors [30]. Initially characterized as an enzyme involved in the dephosphorylation of O-phospho-L-serine to L-serine [31], MtSerB2 has been recently shown to be secreted into the cytoplasm of infected THP1 cells and is hypothesized to help the bacterium in immune invasion and evasion [30].…”
Section: Serb2mentioning
confidence: 99%
See 2 more Smart Citations
“…SerB2 is the most recent addition in the repertoire of Mtb's secreted virulence factors [30]. Initially characterized as an enzyme involved in the dephosphorylation of O-phospho-L-serine to L-serine [31], MtSerB2 has been recently shown to be secreted into the cytoplasm of infected THP1 cells and is hypothesized to help the bacterium in immune invasion and evasion [30].…”
Section: Serb2mentioning
confidence: 99%
“…Initially characterized as an enzyme involved in the dephosphorylation of O-phospho-L-serine to L-serine [31], MtSerB2 has been recently shown to be secreted into the cytoplasm of infected THP1 cells and is hypothesized to help the bacterium in immune invasion and evasion [30]. SerB2 belongs to the haloacid dehalogenase (HAD) class of enzymes.…”
Section: Serb2mentioning
confidence: 99%
See 1 more Smart Citation
“…Through suppressing NF-κB activation, M. tuberculosis favors production of anti-inflammatory cytokines by epithelial cells, such as IL-22 and IL-10. 140 Shree and colleagues 141 reported that Rv3042c (also known as MtSerB2), a bacterial haloacid dehalogenase phosphatase, interacts with HSP90, HSP70, and HSP27 and inhibits apoptotic pathways in host cells, which in turn has been shown to be required for mycobacterial elimination. 142 Indeed, MtSerB2 dephosphorylates NF-κB and MAPK-p38, which results in cell deactivation and failure of host resistance against M. tuberculosis.…”
mentioning
confidence: 99%
“…142 Indeed, MtSerB2 dephosphorylates NF-κB and MAPK-p38, which results in cell deactivation and failure of host resistance against M. tuberculosis. Pharmacologic inhibition of MtSerB2 with clofazimine, a drug used for the treatment of extensively drug resistant and multidrug resistant TB cases, is thought to successfully restore antimycobacterial cellular response, 141 reinforcing the idea that M. tuberculosis directly dampens NF-κB activation to suppress host resistance.…”
mentioning
confidence: 99%